BGP scaling techniques revisited. - Scudder, John G.
This note adds definitions and clarification to "A Comparison of Scaling Techniques for BGP" [1], corrects some minor errors and clarifies points which may not have been clear in the original paper. It also adds a new analysis of the scaling properties of route-reflectors and confederations, leading to a new conclusion that route-reflection and confederations scale equally well in the general case and that the choice of the scaling technique employed by a network needs to be made on a basis other than the scalability metric we have analyzed.